PENGARUH PENGGUNAAN MEDIA SOSIAL INSTAGRAM TERHADAP EFEKTIVITAS PESAN DAKWAH PADA MAJELIS MULAZAMAH MAHASISWA MUSH'AB BIN UMAIR DI SURAKARTA TAHUN 2022 - Usamah Jundu Rohman; Arif Effendi (Jurnal Inovasi Penelitian, 2022)
Usamah Jundu Rohman and Arif Effendi, Thesis, The effect of using instagram social media on the effectiveness of dakwah messages at the mulazamah assembly of mush’ab bin umair students in Surakarta in 2022, Surakarta Mamba’ul ‘Ulum of Islamic Institute. This research wish to know the use of instagram social media at mus’ab bin umair student council in Surakarta in 2022 ; wish to know the effectiveness of dakwah message at the student mulazamah council of mus’ab bin umair in Surakarta in 2022 ; and wish to know correlation between the using of instagram social media and the effectiveness of dakwah message at the student mulazamah council of Mus’ab bin Umair in Surakarta in 2022. This research is a type of correlational quantitative research that correlates two variables. Subjects in this study are followers of the Instagram account @mulazamahmushab which is the official Instagram account belonging to the Mush'ab bin Umair Student Student Council with a population of 12,176. The data analysis technique to test the hypothesis in this study is to use the Product Moment correlation analysis technique. The results showed that the use of instagram social media at the mush'ab bin umair mulazamah council in Surakarta in 2022, was in the good category; the effectiveness of dakwah messages is in the effective category ; the results of correlation are r xy = 0.672 or the category is questionable.